Collaborative Policing to Combat Cyber Crime in Banking Sector Modelling – a Systematic Literature Review - Sabu, Wani; Wahyurudhanto, Albertus; Puspitasari; Pratama, Bambang (Dinasti Research, 2025)
This study addresses the increasing threats of cybercrime that endanger the stability of banking industry, driven by the rapid growth of digital financial transactions. The objective of this research is to formulate a collaborative policing model to effectively prevent and respond to cybercrime within the banking sector. The research was conducted through a comprehensive literature study that explored various aspects of cybersecurity, inter-agency collaboration, technology management, and the roles of actors in cyberspace. The findings indicate that an effective collaborative policing strategy requires the integration of multiple components such as initial conditions, motivation, key actors, emerging technologies, vulnerabilities, international legal frameworks, cyber diplomacy, collaborative processes, and outcome governance. The collaboration process must be built on open dialogue, strong commitment, mutual trust, and shared consensus to create adaptive and sustainable cyber resilience. The conclusion of this study is that a collaborative policing model can serve as a strategic approach to enhance the effectiveness of cybercrime prevention and response efforts in Indonesia’s digital financial sector